2010
DOI: 10.1111/j.1439-0507.2009.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinea incognito due to Trichophyton mentagrophytes

Abstract: Tinea incognito is a dermatophytosis of atypical clinical character, usually misdiagnosed and treated with corticosteroids. We report a case of tinea faciei modified by high potency topical corticosteroids in a 54-year-old woman. Deep, intense inflammatory plaque with boggy, pustular surface located on the right cheek was found. Direct microscopy and culture confirmed dermatophytosis and led to the identification of Trichophyton mentagrophytes var. mentagrophytes. Complete resolution occurred after treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
2
14
0
3
Order By: Relevance
“…Topical corticosteroids allow fungi to grow readily, and alter the clinical feature of the lesions, because they have immunosuppressive activity5. Regretfully, glucocorticosteroids are extensively used by patients and non-dermatologists, and lead to long-lasting fungal infections1, similar to that which occurred in our case.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Topical corticosteroids allow fungi to grow readily, and alter the clinical feature of the lesions, because they have immunosuppressive activity5. Regretfully, glucocorticosteroids are extensively used by patients and non-dermatologists, and lead to long-lasting fungal infections1, similar to that which occurred in our case.…”
supporting
confidence: 61%
“…The clinical features of tinea faciei are characterized by various morphology, and because of that, the entity can mimic many other cutaneous disorders1. Moreover, because tinea faciei is relatively uncommon when compared with other forms of superficial fungal infection, it is often misdiagnosed; and treated with glucocorticosteroids, not antifungal agents1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of misdiagnosis, tinea facei is often treated with topical steroids and can lead to a clinical presentation called T. incognito. [1][2][3][4][5][6][7][8][11][12][13][14] Administration of potent topical steroids before microbiological diagnosis is one of the biggest problems in the management of fungal infections. It has been demonstrated that potent topical steroids can increase the numbers of hyphae present on the surface of the skin in fungal infections and change the appearance of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Tinea incognito should be included in the differential diagnosis of suppurative skin infections, especially when they have earlier been treated by local topical corticosteroids without response. [1][2][3][4]7,[11][12][13][14][15][16][17][18] Therefore, in order to prevent unnecessarily use of steroids for the facial infections, we strongly suggest making mycological examination.…”
Section: Discussionmentioning
confidence: 99%